PENENTUAN SANKSI PIDANA DALAM SUATU UNDANG-UNDANG - AR, Suhariyono (Direktorat Jenderal Peraturan Perundang-undang, Kementerian Hukum dan Hak Asasi Manusia, 2009)
Criminal sanction as a suffering or pain (for the criminals) must be carefullyconsidered by the lawmakers to fix or determine a kind and the quantity ofsentence in a bill, especially for criminalization concerning maladministrationor civil action. Actually, up to now, there is no completely guideline for thecriminalization, however the lawmakers should consider realistically andproportionally in determining the asking of criminal policy, whether it isretaliation or construction. The sanction measures should compare to anotherbills or the bills in another countries. So, a fairness value is not only belongsto the judges, but also belongs to the lawmakers (legislators).